SIX SIGMA FRAMEWORKS: AN ANALYSIS BASED ON ROGERS’ DIFFUSION OF INNOVATION THEORY - Kifayah Amar (Jurnal Ilmiah Teknik Industri, 2012)
This paper attempt to analyze frameworks related to Six Sigma and Lean Six Sigma. The basis of analysis the frameworks is the diffusion of innovation theory. Several criteria was used to analyze the frameworks e.g. relative advantage, compatibility, complexity, trialability, observability, communication channels, nature of the social system/culture and extent of change agent.    Based on framework analysis, there is only one framework fits to Rogers’ theory on diffusion of innovation. The framework is a Lean Six Sigma framework which consists elements such owner/manager commitment and involvement, employee involvement, training, culture change and external support. Even though the elements have similarity to other Six Sigma frameworks but they put more attention on culture change and external support. Generally speaking, the culture change and external support are the most important elements to the implementation of Six Sigma or other soft approaches particularly for small organizations.